Implementation of the Village Financial System Application (Siskeudes) version 2.0.6b in Jombang Regency - Nurhayati, Titin; Dwirini, Dwirini (Formosa Journal of Applied Sciences, 2024)
The purpose of this article is to study how the Siskeudes Application version 2.0.6b is used in Jombang Regency. Qualitative research is what is used. Observations, interviews and documentation were used to obtain primary data. The informants in this research were the Village Assistant, Ngumpul Village Secretary, and Pulosari. The study results show that 1) The implementation of the Siskeudes Application version 2.0.6b in Jombang Regency is in accordance with Minister of Home Affairs Regulation No. 20 of 2018 concerning Village Financial Management; 2) Village government performance has improved during the implementation of the Siskeudes Application version 2.0.6b in Jombang Regency; and 3) in accordance with the objectives of implementing the Siskeudes Application, namely to make it easier for village governments to plan, implement and execute. 4) One crucial thing is the payment of incorrect tax which does not appear in the Tax Assistant's Cash Book.